Handshake, No. 7 (October 2012) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: road: Brazils competitive drive; rail: speeding toward tomorrow; logistics: MIT expert on why logistics clusters matter; and interview: UPSs sustainable strategies.